Quantitative scenarios for cascading risks in AI, climate, synthetic bio, and financial markets by 2075 - Undheim, Trond Arne; Ahmad, Taimur (Frontiers in Complex Systems, 2024)
Humanity faces a myriad of existential technology, geopolitical, and ecological risks. The paper analyzes the possibility that negative shocks superimpose and multiply their effects, leading to catastrophic macro-dynamics.This paper presents a rare, quantitative scenario model superimposed upon narrative scenarios where the cascading effects of 19 quantitative indicators of growth or decline are projected into 2075. These indicators map onto five narrative scenarios, and are subsequently re-combined to study effects of plausible cascading risk events coming to pass in the 50 year period between 2025 and 2075. Results indicate that even in the case of deeply catastrophic events, the world would eventually recover within 25 years, as has historically been the case. The exception is that in the event of several catastrophic events in short order around the midpoint of the 50-year scenario timeline, the cascading risk escalation would create chaos effects or negative cascades. The possibility of a protracted depression and no visible recovery within 25 years is the result. If we assume a modest interaction effect, even with just 3-5 co-occurring catastrophes, the result becomes a path towards humanity's extinction. The uncertainty of these projections must be clearly stated given the amount of model assumptions they rely upon. Further study should be conducted with a larger set of indicators.